Preparation method of defective graphene negative electrode for lithium battery
By irradiating natural graphite powder with high current pulsed electron beams, defects are generated and mutual peeling between graphite layers are achieved, and high-performance defective graphene negative electrode material is prepared, which solves the problems of poor circulation performance and impurities introduction in the prior art, and realizes an efficient and stable lithium-ion battery negative electrode material.
Patent Information
- Application Number
- CN202411870767.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
When the prior art improves graphite for the negative electrode material of lithium-ion battery, it is difficult to achieve structural defects and interlayer peeling at the same time, resulting in poor circulation performance and introduction of impurities.
The natural graphite powder is irradiated with high current pulsed electron beams, defects are generated and mutual peeling between graphite layers are achieved, defective graphene anode material is prepared, and it is mixed with conductive agent and binder and then coated on metal foil.
The storage capacity and cycle stability of the negative electrode of the lithium-ion battery are significantly improved, more lithium-ion diffusion channels are provided, the ion diffusion path is shortened, and the introduction of impurities is avoided, achieving an efficient and environmentally friendly preparation method.
Smart Images

Figure CN119650602A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery negative electrode technology, and in particular to a method for preparing a defective graphene negative electrode for a lithium battery. Background Art
[0002] Graphite has many advantages as anode material for lithium-ion batteries, such as good conductivity, environmental friendliness and high theoretical capacity (372 mAh / g), but it also has some limitations. For example, the surface microstructure of graphite is rough and porous, and its compatibility with electrolytes is poor; during the charge and discharge process, due to the co-embedding of solvent molecules, problems such as volume expansion and structural collapse will occur, resulting in poor cycle performance. In addition, the conventional hexagonal layered structure of graphite also limits the rate performance, energy density and power density of lithium-ion batteries.
[0003] At present, the methods for modifying the graphite structure mainly include exfoliating graphite to obtain high-quality graphene and constructing defects in the graphite structure. Although these methods have improved the performance of lithium-ion batteries to a certain extent, there are still some problems. For example, although most chemical methods can increase the lithium storage capacity, they will introduce complex oxygen-containing functional groups and cannot fundamentally solve the problem of cycle stability. In addition, the structure is unstable due to uneven doping of heteroatoms, which causes the capacity to decay during the cycle. Among physical methods, such as laser beams and ion beams, although they can generate defects in the graphite structure in situ, they cannot achieve mutual exfoliation between graphite layers. Therefore, it is necessary to propose a new solution to solve the above problems. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing a defective graphene negative electrode for a lithium battery, which does not introduce complex oxygen-containing functional groups during the preparation process, and while defects are generated in the graphite structure, the mutual exfoliation of graphite layers is achieved.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for preparing a defective graphene negative electrode for a lithium battery comprises the following steps:
[0007] (1) Grinding natural graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a high current pulse electron beam device, starting the device, activating the magnetic field, the spark source and the cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with the cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 9-15 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 -3Pa, acceleration voltage is 25KV, pulse number is 1-2 times, pulse duration is 1-3μs, energy density is 2.5J / cm 2 ;
[0008] (2) The defective graphene negative electrode material obtained in step (1) is mixed with a conductive agent and a binder in a mass ratio of (90-92): (1-2): (5-7), and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a metal foil to prepare a defective graphene negative electrode for a lithium battery.
[0009] As a preferred embodiment, the natural graphite is natural flake graphite.
[0010] As a preferred solution, the model of the high current pulse electron beam device is HOPE-I.
[0011] As a preferred solution, the conductive agent is carbon black.
[0012] As a preferred solution, the binder is PVDF.
[0013] As a preferred solution, the metal foil is copper foil.
[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0015] Natural graphite is modified by high-current pulsed electron beam irradiation, and its surface undergoes significant expansion and deformation. While defects are generated in the graphite structure, the graphite layers are peeled off from each other, so that the entire surface of the graphite presents a hairy wrinkled morphology and the structure is almost transparent, which significantly improves the storage capacity and cycle stability. In addition, the obtained defective graphene negative electrode material not only provides more channels for lithium ion diffusion, but also the internal voids effectively shorten the ion diffusion path. In addition, the high-current pulsed electron beam irradiation method used in the present invention is a physical method, which does not require the use of specific reducing agents, oxidizing agents or other intermediate media, avoids the introduction of impurities, and is an efficient and environmentally friendly preparation method.
[0016] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments: BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a scanning electron microscope image of the defective graphene negative electrode material in Example 1 of the present invention;
[0018] Figure 2 It is a cycle curve diagram of Example 1 of the present invention and a comparative example. DETAILED DESCRIPTION
[0019] The present invention discloses a method for preparing a defective graphene negative electrode for a lithium battery, comprising the following steps:
[0020] (1) Grinding natural graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a high current pulse electron beam device, starting the device, activating the magnetic field, the spark source and the cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with the cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 9-15 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 -3 Pa, acceleration voltage is 25KV, pulse number is 1-2 times, pulse duration is 1-3μs, energy density is 2.5J / cm 2 Specifically, the natural graphite is natural flake graphite, and the model of the high current pulsed electron beam device is HOPE-I.
[0021] (2) The defective graphene negative electrode material obtained in step (1) is mixed with a conductive agent and a binder in a mass ratio of (90-92): (1-2): (5-7), and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a metal foil to prepare a defective graphene negative electrode for a lithium battery; specifically, the conductive agent is carbon black, the binder is PVDF, and the metal foil is copper foil.
[0022] The following is an explanation with reference to specific embodiments and comparative examples.
[0023] Example 1
[0024] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 12 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 - 3 Pa, acceleration voltage is 25KV, pulse number is 1, pulse duration is 2μs, energy density is 2.5J / cm 2 .
[0025] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 91.6:1.8:6.6, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0026] Example 2
[0027] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 12 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 - 3 Pa, acceleration voltage is 25KV, pulse number is 2 times, pulse duration is 1μs, energy density is 2.5J / cm 2 .
[0028] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 90:1:6.3, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0029] Example 3
[0030] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 9 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 - 3 Pa, acceleration voltage is 25KV, pulse number is 2 times, pulse duration is 3μs, energy density is 2.5J / cm 2 .
[0031] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 91.5:1.5:5, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0032] Example 4
[0033] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 15 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 - 3 Pa, acceleration voltage is 25KV, pulse number is 2 times, pulse duration is 3μs, energy density is 2.5J / cm 2 .
[0034] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 92:2:5.3, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0035] Example 5
[0036] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 9 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 - 3 Pa, acceleration voltage is 25KV, pulse number is 1, pulse duration is 3μs, energy density is 2.5J / cm 2 .
[0037] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 92:1.5:7, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0038] Example 6
[0039] (1) Grinding natural flake graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a HOPE-I high current pulse electron beam device, starting the device, activating the magnetic field, spark source and cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with a cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 15 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10- 3 Pa, acceleration voltage is 25KV, pulse number is 1, pulse duration is 2μs, energy density is 2.5J / cm 2 .
[0040] (2) The defective graphene negative electrode material obtained in step (1) is mixed with carbon black and PVDF in a mass ratio of 91.5:2:6, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a defective graphene negative electrode for a lithium battery.
[0041] Comparative Example
[0042] (1) After natural flake graphite is ground into natural graphite powder with a particle size of 12 μm, it is mixed with carbon black and PVDF in a mass ratio of 91.6:1.8:6.6, and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a copper foil to prepare a lithium battery negative electrode.
[0043] The negative electrodes prepared in the above examples and comparative examples were assembled into lithium ion half-cells in a glove box and the electrochemical performance was tested at a current density of 0.2C. The test results are shown in Table 1. Figure 2 It is a cycle curve diagram of Example 1 and the comparative example.
[0044]
[0045] Table 1
[0046] The above data are analyzed. The defective graphene negative electrode for lithium battery prepared by the preparation method of the present invention has a much better gram capacity and capacity retention rate than the lithium battery negative electrode prepared by unmodified natural graphite. Figure 2 , the blue curve represents the charge and discharge efficiency curve of the defective graphene negative electrode for lithium battery prepared in Example 1, and its charge and discharge efficiency is very high and stable, close to 100%. The red curve is the charge and discharge cycle efficiency curve of the defective graphene negative electrode for lithium battery prepared in Example 1, and the green curve is the charge and discharge cycle efficiency curve of the negative electrode of lithium battery prepared in the comparative example. Figure 2It can be clearly seen that under the constant current charge and discharge cycle at a current density of 0.2C, the overall reversible capacity of the comparative example shows a downward trend, and it drops to 122.5mAh / g after 500 cycles. In contrast, the curve of Example 1 first drops, then rises, and finally shows a downward trend. After 200 cycles, its reversible capacity rises to 418.95mAh / g, which has exceeded the theoretical lithium storage capacity of graphite. Subsequently, after 500 cycles, the capacity drops to 397.6mAh / g, and the capacity retention rate is 94.5%. From the comparison of the cycle performance of Example 1 and the comparative example, it can be concluded that the defective graphene negative electrode for lithium batteries prepared by the preparation method of the present invention not only has excellent performance, but also achieves unexpected results.
[0047] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a defective graphene negative electrode for a lithium battery, characterized in that: The following steps are included: (1) Grinding natural graphite into natural graphite powder and compressing it into a stainless steel container, then fixing the stainless steel container containing the natural graphite powder on a high current pulse electron beam device, starting the device, activating the magnetic field, the spark source and the cathode high voltage power supply in sequence, and directly irradiating the natural graphite powder with the cathode emission electron beam to obtain a defective graphene negative electrode material; wherein the particle size of the natural graphite powder is 9-15 μm, and the process parameters of the high current pulse electron beam device are as follows: the vacuum degree is 6.5×10 -3 Pa, acceleration voltage is 25KV, pulse number is 1-2 times, pulse duration is 1-3μs, energy density is 2.5J / cm 2 ; (2) The defective graphene negative electrode material obtained in step (1) is mixed with a conductive agent and a binder in a mass ratio of (90-92): (1-2): (5-7), and an NMP solution is added to prepare a slurry. Then, the slurry is coated on a metal foil to prepare a defective graphene negative electrode for a lithium battery.
2. The method for preparing a defective graphene negative electrode for a lithium battery according to claim 1, characterized in that: The natural graphite is natural flake graphite.
3. The method for preparing a defective graphene negative electrode for a lithium battery according to claim 1, characterized in that: The model of the high current pulse electron beam device is HOPE-I.
4. The method for preparing a defective graphene negative electrode for a lithium battery according to claim 1, characterized in that: The conductive agent is carbon black.
5. The method for preparing a defective graphene negative electrode for a lithium battery according to claim 1, characterized in that: The binder is PVDF.
6. The method for preparing a defective graphene negative electrode for a lithium battery according to claim 1, characterized in that: The metal foil is copper foil.
Citation Information
Cited By
Super capacitor based on curved surface graphene composite electrode and preparation method thereof
CN120565304A
Super-capacitor based on curved graphene composite electrode and preparation method thereof
CN120565304B